2011
DOI: 10.1097/ta.0b013e3182288783
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair Compared With Operative Repair of Traumatic Rupture of the Thoracic Aorta: A Nonsystematic Review and a Plea for Trauma-Specific Reporting Guidelines

Abstract: The lack of reporting guidelines coupled with a paucity of follow-up data weakens any recommendation regarding the optimal choice of intervention. To address these deficiencies, we recommend reporting guidelines specific to the trauma population that will allow better risk adjustment and improve the quality of the evidence base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 89 publications
2
23
0
7
Order By: Relevance
“…As far as delayed intervention is concerned, based on the findings of Demetriades et al (2009) described above, Karmy-Jones et al suggest delaying repair for patients with either significant injury or reversible physiologic derangement [36,40].…”
Section: Non-systematic Reviewsmentioning
confidence: 94%
See 4 more Smart Citations
“…As far as delayed intervention is concerned, based on the findings of Demetriades et al (2009) described above, Karmy-Jones et al suggest delaying repair for patients with either significant injury or reversible physiologic derangement [36,40].…”
Section: Non-systematic Reviewsmentioning
confidence: 94%
“…Importantly, the fact that unstable patients mostly underwent surgical repair biases the outcomes, according to the authors [40]. Even though ISS were similar between the groups, the authors found that only about half of the studies included described injury severity by ISS and about a third provided details on haemodynamic stability.…”
Section: Non-systematic Reviewsmentioning
confidence: 95%
See 3 more Smart Citations